Environment–attitude relationships: girls in inquiry-based mathematics classrooms in the United Arab Emirates - Robinson, Jennifer M.; Aldridge, Jill (2022)
Girls’ attitudes towards mathematics can impact their achievement and career choices in STEM fields. Can the introduction of inquiry-based learning (IBL) in mathematics classes generate positive associations between girls’ perceptions of the learning environment and their attitudes towards mathematics? Based in the United Arab Emirates, this study provided important information about the relationships between learning environment factors central to an inquiry method and student engagement. Data collection involved administering two surveys to female mathematics students (N = 291) in four schools: one to assess students’ perceptions of the learning environment and another to assess students’ attitudes towards mathematics. Positive and statistically-significant (p <.01) associations emerged between learning environment factors important to an inquiry approach and students’ attitudes. These findings provide important information about how IBL might improve girls’ attitudes towards mathematics classes and whether IBL environments are related to their attitudes.